The Hualong-1 project in Argentina: a case study on the economic, technological, and geopolitical complexities of the belt and road initiative - Gao, Ge (Frontiers in Political Science, 2025)
China’s Belt and Road Initiative (BRI) offers major opportunities for trade, investment, and connectivity, yet these are accompanied by structural challenges such as debt sustainability, limited transparency, and uneven technology transfer. The Hualong-1 nuclear power project in Argentina illustrates these tensions, reflecting the interplay between domestic vulnerabilities and global geopolitical dynamics. Using grounded theory and in-depth elite interviews, this study analyzes Argentina’s nuclear cooperation with China under the BRI through political, economic, and technological lenses. Findings reveal that Argentina’s chronic macroeconomic instability, political fluctuations, and social-environmental opposition undermine project viability. The turnkey contract model further restricts technology transfer, resulting mainly in local assembly under Chinese supervision and limiting Argentina’s pursuit of nuclear autonomy. Geopolitically, the Hualong-1 project is shaped by the intensifying U.S.-China rivalry, constraining Argentina’s policy space and amplifying its dependence. The study concludes that Argentina’s engagement under the BRI embodies a complex rationality where national ambitions, economic constraints, and external power competition continuously interact.